Corticospinal Plasticity in Bilateral Primary Motor Cortices Induced by Paired Associative Stimulation to the Dominant Hemisphere Does Not Differ between Young and Older Adults - Daina S. E. Dickins; Marc R. Kamke; Martin V. Sale (Neural Plasticity)
Older adults have been shown to exhibit a reduction in the lateralization of neural activity. Although neuroplasticity induced by noninvasive brain stimulation has been reported to be attenuated in the targeted motor cortex of older adults, it remains possible that the plasticity effects may instead manifest in a more distributed (bilateral) network. Furthermore, attention, which modulates neuroplasticity in young adults, may influence these effects. To address these questions, plasticity was induced in young (19–32 years) and older (65–78 years) adults using transcranial magnetic stimulation (TMS) paired with peripheral nerve stimulation. The plasticity effects induced by this paired associative stimulation (PAS) protocol in the targeted and nontargeted hemispheres were probed using TMS-induced motor-evoked potentials (MEPs) recorded from the abductor pollicis brevis (APB) muscle of each hand. PAS-induced effects were highly variable across individuals, with only half of the participants in each group demonstrating the expected increase in MEP amplitude. Contrary to predictions, however, PAS-induced corticospinal plasticity manifests predominately in the targeted hemisphere for both young and older adults. Attention to the target hand did not enhance corticospinal plasticity. The results suggest that plasticity does not manifest differently across bilateral corticospinal pathways between young and older adults.